Healthy Environmental Parameters as the Identification of Mining Entities - Siti Setyawati Kartika Sari; Raden Roro Widya Ningtyas Soeprajitno (Institute of Research and Community Outreach - Petra Christian University, 2021)
Nowadays the biggest global problem in the industry sector is located on environmental issues. This issue committed by the national entities that produced a lot of waste and emission. To answer this problem, the government decided to make a commitment for building policies of zero emission in the year 2050 accompanied with the appeal for disclosing and reporting the Sustainability Report for the entities in the industry sector. This research will elucidate the effort of entities involved for dealing with the global waste issue of industry sector. The involvement will be evaluated in the disclosure that made using the applicable Global Reporting Index scale. This research utilized mining sector entities listed in IDX from 2014 - 2018. Furthermore, this research used content analysis with processing multiple linear regression and applied the software of Stata 14. The outcome of this research is to attain the effort enhancement of improving the mining entities and the disclosure was greatly influenced by certain parameters, so it showed the significant difference from each mining entity. This research is expected could contribute to the government so they are more concerned by paying more attention and making policies to synergize the goal of “zero waste and zero emission” by a healthy-environment-performance basis for the entities, and augment the theory application along with knowledge development of disclosure in form of Sustainability Report. Keywords: Environment; Waste; Emission; Sustainability Report; Mining Entities.